2016
DOI: 10.1007/s10815-016-0678-4
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse variables and embryo gender: a retrospective analysis of 81 live births obtained following minimal stimulation and single embryo transfer

Abstract: Although the sample size of our cohort was limited, our findings suggest that several expanded blastocyst stage morphokinetic parameters are associated with female embryo gender. If confirmed on a larger sample these could be potentially used to increase the proportion of female embryos among non-invasively selected blastocysts following single embryo transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Bronet and colleagues were able to build a hierarchical model based on s2 (t4-t3)<2 h and tM between 80.8–98.3 h, that increased the likelihood -though not significant- of selecting female embryos after cleavage stage biopsy on day 3 [ 64 ]. Another study explored TLM parameters and gender in untested blastocysts based on the gender upon live birth and concluded that female embryos are strongly associated with late expanded blastocyst TLM parameters [ 65 ]. However, as untested blastocysts were not only transferred in HRT cycles but also in natural cycles, it cannot be guaranteed that all live births were obtained from the respective transferred blastocyst or were obtained from spontaneous pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Bronet and colleagues were able to build a hierarchical model based on s2 (t4-t3)<2 h and tM between 80.8–98.3 h, that increased the likelihood -though not significant- of selecting female embryos after cleavage stage biopsy on day 3 [ 64 ]. Another study explored TLM parameters and gender in untested blastocysts based on the gender upon live birth and concluded that female embryos are strongly associated with late expanded blastocyst TLM parameters [ 65 ]. However, as untested blastocysts were not only transferred in HRT cycles but also in natural cycles, it cannot be guaranteed that all live births were obtained from the respective transferred blastocyst or were obtained from spontaneous pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-associated morphokinetics at later stages of embryonic development has also been a topic of ongoing debate. For example, a recent retrospective analysis showed an increase in time to reach the fully expanded blastocyst stage in male embryos [23], while other studies have found that the development of male embryos was faster than female embryos, as "t3 had a significant correlation with live birth sex" [24]. Meanwhile, Serdarogullari et al [25] found no statistical significance in the kinetic profiles between sexes, from early cleavage events through to the blastocyst stage.…”
Section: Discussionmentioning
confidence: 96%
“…Results indicated that female status is related to late cleavage (t8), morula (tM), and blastocyst-stage morphokinetic parameters. The authors concluded that some expanded blastocyst-stage morphokinetic variables are correlated with female embryo gender [25]. Otherwise, in another study 176 male and 161 female embryos were evaluated, and there were remarkable diferences between embryo developmental time points and intervals regarding gender.…”
Section: Efect Of Gender Status On Embryo Morphokineticsmentioning
confidence: 93%